Molecular systematics of the South American rodent Calomys laucha (Cricetidae: Sigmodontinae), a reservoir of the Laguna Negra hantavirus - González Ittig, Raúl Enrique (2014)
The small vesper mouse (Calomys laucha (Fischer, 1814)) (Cricetidae: Sigmodontinae) ranges widely in Brazil, Uruguay, Paraguay, Argentina, and Bolivia. The species is the reservoir of the Laguna Negra hantavirus (LNV) in Paraguay but not in Argentina, where it is one of the most abundant rodents in agro-pastoral ecosystems. To answer the question if the nominal species C. laucha constitutes a single genetic unit or if it presents genetic discontinuities that may relate to hosting LNV, we sequenced the cytochrome b (cyt b) gene of specimens from throughout the range of the distribution of the species. Phylogenetic analyses revealed two well-supported clades. Twenty-two sequences from Argentina, Paraguay, and Bolivia grouped in clade A, but three sequences from Uruguay and Brazil clustered in a quite divergent clade B. The genetic distance between the two groups is 5.75%. No significant differences between Argentinean, Paraguayan, and Bolivian specimens assigned to C. laucha were detected. The restricted distribution of LNV associated to C. laucha in central Paraguay could be explained by a “natural nidality” phenomenon.